Effect of Diabetes Mellitus on Clinical Outcomes and ST Segment Resolution in Patients with ST Segment Elevation Myocardial Infarction Treated with Streptokinase - Iqbal, Shahriar; Bari, M Saiful; Akter Ruby, Nazbin (Journal of the Medical College for Women & Hospital, 2026)
Background: Diabetes mellitus (DM) has a major impact on clinical outcomes for coronary artery disease (CAD), which continues to be a major source of morbidity and mortality worldwide. Diabetes mellitus (DM) worsens atherosclerosis and hinders myocardial recovery in patients with ST-segment elevation myocardial infarction (STEMI), which may have an impact on the results of streptokinase thrombolysis. Aim: The study aimed to examine the clinical outcomes and ST-segment resolution in diabetic STEMI patients receiving streptokinase treatment patients. Materials and Method: This cross-sectional study examined the clinical outcomes and ST-segment resolution of 50 diabetic and 50 non-diabetic STEMI patients receiving streptokinase treatment at Mymensingh Medical College Hospital between December 2016 and November 2017. Direct interviews, Electrocardiographs (ECGs), echocardiograms, and laboratory tests were all used in the data collection process. There were three categories for ST-segment resolution: unsuccessful (<30%), partial (30–70%), and complete (>70%). The statistical analysis was conducted using SPSS version 20, with a significance threshold of p<0.05. Results: The diabetes group had greater rates of unsuccessful resolution (42% vs. 12%, p=0.001) and considerably lower rates of complete ST-segment resolution (28% vs. 52%, p=0.001). Diabetics had a considerably reduced mean left ventricular ejection fraction (LVEF) (46.54±10.17 vs. 51.64±8.48, p=0.008). Longer hospital stays (60% vs. 40%, p=0.006) and cardiogenic shock (44% vs. 24%, p=0.005) were more common in diabetics. Overall, diabetic patients fared poorly, even though anterior myocardial infarction was the most frequent site in both groups. These results are consistent with earlier studies that linked diabetes mellitus to worse cardiac recovery and systemic outcomes following thrombolysis. Conclusion: In STEMI patients receiving streptokinase treatment, diabetes mellitus substantially compromises ST-segment resolution, myocardial function, and clinical results. For diabetes patients to recover as best they can, tailored interventions are crucial. To confirm these results and investigate more sophisticated diagnostic and treatment strategies, more multicenter research is required. J Med Coll Women Hosp.2026; 22(1): 149-155